The Knot : outdoor weddings : fresh ideas for events in gardens, vineyards, beaches, mountains, and more - Roney, Carley (Potter Style, 2015)
"In any outdoor setting--beach or backyard, vineyard or mountaintop--the couple has unlimited opportunity to personalize their day and create unforgettable ambience. The 50 real weddings featured in The Knot Outdoor Weddings were inspired by twinkling lights and cityscapes, fresh herbs and countryside farmers' markets, shells and the sea, mountain peaks and endless vistas. These gorgeous celebrations reveal the keys to making the most of your setting's natural beauty, while infusing it with special, meaningful touches that are all your own. The Knot Outdoor Weddings also includes location-specific planning advice for the details of your event, such as attire, color patlettes, stationery, menu, and favors, as well as considerations for perfecting your plan B and keeping guests comfortable in any weather"--publisher